Cell Envelope Integrity and Capsule Characterization of Rhodotorula mucilaginosa Strains from Clinical and Environmental Sources - Johnathan Yockey (American Society for Microbiology, 2019)
ABSTRACT Rhodotorula yeasts are pink, encapsulated basidiomycetes isolated from a variety of environments and clinical settings. They are increasingly linked with disease, particularly central venous catheter infections and meningitis, in immunocompromised patients. Eight clinical and eight environmental strains molecularly typed as Rhodotorula mucilaginosa were compared to six Cryptococcus neoformans strains for phenotypic variability. Growth on cell integrity-challenging media suggested that R. mucilaginosa cells possess differences in signaling pathways, cell wall composition, or assembly and that their membranes are more susceptible to perturbations than those of C. neoformans. All 16 R. mucilaginosa strains produced urease, while none produced melanin with l-3,4-dihydroxyphenylalanine (l-DOPA) as a substrate. India ink staining reveals that clinical R. mucilaginosa capsules are larger than environmental capsules but that both are generally smaller than C. neoformans capsules. All R. mucilaginosa strains were resistant to fluconazole. Only two clinical strains were susceptible to voriconazole; all of the environmental strains were resistant. We generated an anticapsular antibody (Rh1) to R. mucilaginosa; Rh1 did not bind C. neoformans control strains, was specific to Rhodotorula species, and bound to all tested Rhodotorula strains. Binding assays performed with wheat germ agglutinin (WGA), concanavalin A (ConA), calcofluor white (CFW), and eosin Y dye (EY) cell surface probes suggested that chitin may be more accessible in R. mucilaginosa but that the total abundance of chitooligomers is less than in C. neoformans. This report describes a novel reagent that can be used to identify Rhodotorula species and lays the foundation for future cell envelope composition analysis. IMPORTANCE Currently, there is very little known about the phenotypic variability within species of Rhodotorula strains and the role of their capsule. Cryptococcus neoformans has been considered the only encapsulated human fungal pathogen, but as more individuals come to live in states of immunocompromised health, they are more susceptible to fungal infections, including those by Rhodotorula. R. mucilaginosa species are some of those most commonly associated with clinical infections. We wanted to know if clinical and environmental strains of R. mucilaginosa demonstrated disparate capsule phenotypes. With limited antifungal options available and clinical Rhodotorula spp. often resistant to common antifungal drugs such as fluconazole, caspofungin (1, 2), and voriconazole (2), a better understanding of the fungal biology could inform the design and use of future antifungal drugs. The generation of an antibody specific to Rhodotorula fungi could be a useful diagnostic tool, and this work presents the first mention of such in the literature.